THE ROLE OF DEPORTER LEARNING STYLES IN OPTIMIZING PROSPECTIVE TEACHERS’ MATHEMATICAL CREATIVE THINKING THROUGH CASE-BASED E-MODULES - Emy Sohilait; Isti Hidayah; Isnarto; Kristina Wijayanti (IAIN Ambon, 2026)
This study aimed to examine the effects of DePorter learning styles and a case method-based group theory e-module on preservice teachers’ mathematical creative thinking ability. Research integrating the DePorter learning style framework with case method-based e-modules in group theory learning within Indonesian higher mathematics education remains limited. This study employed a quantitative approach using a quasi-experimental nonequivalent control group design. The participants were 52 students of the Mathematics Education Program at STKIP Gotong Royong Masohi, consisting of 30 students in the experimental group and 22 students in the control group. The research instruments included a DePorter learning style questionnaire, a mathematical creative thinking test (Content Validity Index/CVI = 0,89; Cronbach’s α = 0,84), and an observation sheet (Cohen’s κ = 0,78). Data were analyzed using the Shapiro–Wilk test, Levene’s test, normalized gain (N-gain), and two-way ANOVA. The results indicated that the experimental group achieved a higher improvement in mathematical creative thinking ability (N-gain = 0.72; high category) than the control group (N-gain = 0,48; moderate category). Two-way ANOVA revealed significant effects of learning style (F(2,46)=5,87; p=0,004; η²p=0,20), e-module type (F(1,46)=8,21; p=0,001; η²p=0,29), and their interaction (F(2,46)=4,65; p=0,013; η²p=0,17) on mathematical creative thinking ability. Students classified as kinesthetic learners obtained the highest mean scores. These findings suggest that a differentiated case method-based e-module has the potential to support the development of preservice teachers’ mathematical creative thinking ability. Keywords: Deporter Learning Style; Mathematical Creative Thinking; E-Module; Case Method; Group Theory.